2001
DOI: 10.1016/s0899-3289(01)00059-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of HIV infection and needle sharing among injecting drug users in Ho Chi Minh City, Viet Nam

Abstract: The HIV prevalence in 1998 among IDUs was 44% for those on the street and 38.5% for those in the rehabilitation center. Independent predictors for HIV infection in IDUs were being injected by drug dealers (for the 1997 sample), injecting on the street, and sharing the drug pots (for the 1998 sample). The reported rate of needle sharing was low and decreased significantly from 20% in 1995 to 12% in 1998 for the sample of IDUs at the street. In the multivariate analysis, predictors for needle sharing for both st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 16 publications
5
31
1
Order By: Relevance
“…Needle sharing in our study was reported by only one-quarter of those injecting drugs, and is considerably less than in other surveys in which up to 70% of injectors in urban settings reported sharing equipment (Hien et al, 2001;Nguyen et al, 2001;Tran et al, 1998). Other reasons for varying rates of sharing may be related to cost, availability of clean needles and concerns about arrest if caught with injection equipment.…”
Section: Discussioncontrasting
confidence: 79%
“…Needle sharing in our study was reported by only one-quarter of those injecting drugs, and is considerably less than in other surveys in which up to 70% of injectors in urban settings reported sharing equipment (Hien et al, 2001;Nguyen et al, 2001;Tran et al, 1998). Other reasons for varying rates of sharing may be related to cost, availability of clean needles and concerns about arrest if caught with injection equipment.…”
Section: Discussioncontrasting
confidence: 79%
“…The fact that the majority of drug-using FSWs in Hanoi began involvement in drugs within the past 6 years (from 1996) and that most started injecting only within the past 4 years (from 1998) probably explains the recent outbreak of HIV among them. Previous studies among IDUs in Hai Phong and Ho Chi Minh City showed that about half the male IDUs had visited FSWs [11,15]. Our qualitative studies among male drug users and FSWs in Hanoi suggested a strong relationship between drug-using FSWs and male drugusing clients and non-client partners [13,14].…”
Section: Discussionmentioning
confidence: 47%
“…Thus, drug use-related characteristics of FSWs have been studied and described thoroughly in these populations [6][7][8][9]. In Vietnam, because the drug use epidemic is relatively current among FSWs and it is difficult to study them, few studies have examined the issue of HIV and drug use among FSWs [2,5,[10][11][12][13][14] and little is known about their drug use behaviors and practices. We conducted a cross-sectional study in Hanoi in 2002 among practising FSWs who were not in drug use or sex worker rehabilitation centers to examine their HIV risk characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a large body of research about the health of drug users, particularly with respect to the spread of HIV and other infectious diseases, has explored individual risk behaviors that are important within this group, often with a limited focus on how living in cities affected these risk behaviors. [19][20][21] Other work has focused on the health of minority populations, groups that have historically been over-represented in urban areas. For example, there is a growing appreciation of the excess burden of cardiovascular disease and diabetes among urban African American populations in the United States.…”
Section: Introductionmentioning
confidence: 99%